Developing Children's Story-Based Digital Comics (Digibarita) to Increase Early Children's Interest in Reading - Medi Kapriany Purwaningrum; Lilis Suryani; Hamid Patilima (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
Low interest among Indonesian children remains a major concern that affects their literacy development. This study aimed to develop and test DIGIBARITA, a digital comic based on childrenâ€™s stories, as an innovative medium to foster reading interest in early childhood education. The research used a Research and Development (R&D) design adapted from the ADDIE model, consisting of analysis, design, development, and implementation. The subjects were 30 children aged 4â€“6 years at TK Islam Najwa, Bekasi, and early childhood teachers as expert validators and evaluators. Data were collected through validation questionnaires, observation sheets, and interviews, then analyzed descriptively using quantitative and qualitative approaches. Results showed that DIGIBARITA was rated â€œvery validâ€ by the material expert (96.25%), media expert (96.87%), and practitioner (98%). Implementation through individual, small group, and large group trials revealed that children actively participated, enjoyed the reading activities, and showed increased interest in retelling stories. Teacher responses placed the media in the â€œvery goodâ€ category with a score of 98.5%, confirming its practicality. In conclusion, DIGIBARITA is feasible, practical, and effective in enhancing early reading interest and may serve as an alternative literacy medium in early childhood education.